2013
DOI: 10.1021/ja400069s
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Tellurium-Free Thermoelectrics: All-Scale Hierarchical Structuring of p-Type PbSe–MSe Systems (M = Ca, Sr, Ba)

Abstract: We present a systematic study of the characterization and thermoelectric properties of nanostructured Na-doped PbSe embedded with 1-4% MSe (M = Ca, Sr, Ba) phases as endotaxial inclusions. The samples were powder-processed by the spark plasma sintering technique, which introduces mesoscale-structured grains. The hierarchical architectures on the atomic scale (Na and M solid solution), nanoscale (MSe nanoprecipitates), and mesoscale (grains) were confirmed by transmission electron microscopy. These structures p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
118
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 138 publications
(135 citation statements)
references
References 37 publications
12
118
1
4
Order By: Relevance
“…Lead chalcogenides are the most studied thermoelectric materials with high ZT values between 1.4 and 2.2, 4,12,[14][15][16] although concerns about Pb (e.g. toxicity) limit their large scale application.…”
Section: -15mentioning
confidence: 99%
See 1 more Smart Citation
“…Lead chalcogenides are the most studied thermoelectric materials with high ZT values between 1.4 and 2.2, 4,12,[14][15][16] although concerns about Pb (e.g. toxicity) limit their large scale application.…”
Section: -15mentioning
confidence: 99%
“…An approach to obtaining high power factors involves manipulation of the density of states through band engineering, including band convergence/degeneracy [4][5][6] or introduction of resonant impurity levels near the Fermi level. 7,8 Methods to block the propagation of phonons include the introduction of point defects, 9,10 second phase nanoprecipitates 11,12 and mesoscale grain boundaries.…”
Section: Introductionmentioning
confidence: 99%
“…The well-known PbSe system [19][20][21][22][23] is now attracting considerable attention as a promising thermoelectric material for high temperature power generation applications. Heavily doped p-type PbSe has shown ZTs as high as ~ 1.2 at 850 K [24,25], while after the simultaneous improvement of both electrical and thermal…”
Section: Introductionmentioning
confidence: 99%
“…properties ZT values of ~ 1.4 -1.6 can be obtained [9,12,25]. Theoretical calculations have suggested that hole-doped PbSe can potentially reach ZT ~ 2 at 1000 K [26] indicating prospects for further performance improvements.…”
Section: Introductionmentioning
confidence: 99%
“…This is achieved by substituting some of the atoms with dopant elements of different valance [7]. Sodium is the most viable p--type dopant [1,2,10,11] for Pb chalcogenides, though its solubility has been shown to be limited [12,13]. Sodium doping results in considerably higher thermoelectric performance of p--type multiphase compounds when the alloys are doped at concentrations greater than the solubility limit of the matrix [2,5,11,14].…”
Section: Introductionmentioning
confidence: 99%